Multiaxial fatigue crack path prediction using critical plane concept - Jafar Albinmousa (Fracture and Structural Integrity, 2015)
Prediction of fatigue crack orientation can be an essential step for estimating fatigue crack path. Critical plane concept is widely used due to its physical basis that fatigue failure is associated with certain plane(s). However, recent investigations suggest that critical plane concept might need revision. In this paper, fatigue experiments that involve careful measurement of fatigue crack were reviewed. Predictions of fatigue crack orientation using critical plane concept were examined. Projected length and angle were used to characterize fatigue crack. Considering the entire fatigue life, this average representation suggests that it is more reasonable to assume the plane of maximum normal strain as the critical plane even though fundamentally the plane of maximum shear strain is more likely to be the critical one at early initiation stage.